Pemodelan Proses Bisnis Sistem Marketplace Penjualan Kebutuhan Ormas Dan Partai Berbasis Website - Telaumbanua, Kristian; Damanik, Florida; Suparnap, Erlanie; Sembiring, Afen Prana (Explorer, 2024)
Indonesian marketplaces have grown rapidly in recent years, especially since 2009 when many types of marketplace applications emerged. With the advancement of technology and easy access to the Internet, some consumers who previously never shopped online are now interested in switching to a digital shopping environment to fulfill their needs. However, there are obstacles for sellers in selling the needs of mass organizations and parties such as sellers only selling at the workplace, promotions are still based on references from buyers who buy in stores, so that sales figures are often not maximized. Therefore, an analysis and design of a website-based marketplace application for selling the needs of mass organizations and parties that can meet the sales needs of parties and mass organizations. This research uses the SDLC (System Development Life Cycle) waterfall method to design a system that produces a design of a marketplace application for selling the needs of mass organizations and parties that can facilitate buyers in making product order transactions and facilitate sellers in selling the needs of mass organizations and parties. This design is expected to be a reference to be developed into an application that can be implemented.